2009
DOI: 10.2337/dc09-0176
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Adiposity Is Associated With Elevated C-Reactive Protein Independent of BMI in Healthy Nonobese People

Abstract: OBJECTIVEThere is debate over the most appropriate adiposity markers of obesity-associated health risks. We evaluated the relationship between fat distribution and high-sensitivity C-reactive protein (hs-CRP), independent of total adiposity.RESEARCH DESIGN AND METHODSWe studied 350 people with abdominal adiposity (waist-to-hip ratio [WHR] ≥0.9 in male and ≥0.85 in female subjects) and 199 control subjects (WHR <0.9 in male and <0.85 in female subjects) matched for BMI and age. We measured hs-CRP and major card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 12 publications
10
60
1
3
Order By: Relevance
“…WHtR was also higher in obese patients with high and medium CVR. Lapice et al observed a relationship between abdominal obesity (WHR, WC) and hsCRP independently of BMI and sex in nondiabetic subjects with abdominal obesity [23]. Arbel et al in a large population (n = 13,033) study found associations between hsCRP and obesity indices such as WC, BMI, BAI, WHR and WHtR, where the strongest correlations were observed for BMI, WC and WHtR [24].…”
Section: Discussionmentioning
confidence: 97%
“…WHtR was also higher in obese patients with high and medium CVR. Lapice et al observed a relationship between abdominal obesity (WHR, WC) and hsCRP independently of BMI and sex in nondiabetic subjects with abdominal obesity [23]. Arbel et al in a large population (n = 13,033) study found associations between hsCRP and obesity indices such as WC, BMI, BAI, WHR and WHtR, where the strongest correlations were observed for BMI, WC and WHtR [24].…”
Section: Discussionmentioning
confidence: 97%
“…The CRP is a well-established marker of cardiovascular risk and studies in adults have shown the influence of obesity, especially central fat accumulation, as an important determinant of this parameter (32). In the present study, CRP was associated mainly with TFM and BF% despite a minimal difference for the other indicators of adiposity.…”
Section: Association Between Adiposity Indicators Metabolic Parametementioning
confidence: 37%
“…As has been previously reported, in our study obese participants had elevated levels of inflammation as measured by CRP at baseline [20,21]. Therefore when evaluating the association between obesity and ANA positivity it is imperative to consider the role of inflammation given that it is typically inflammatory conditions such as lupus that induce ANA positivity.…”
Section: Discussionmentioning
confidence: 58%
“…A major difference between the two groups is body habitus where those with the metabolic syndrome have higher rates of abdominal adiposity [19]. Central adiposity has been shown to be associated with higher rates of C-reactive protein (CRP), a common measure of systemic inflammation, in all age groups as well as in people with normal BMI who have higher abdominal fat deposits [20][21][22].…”
Section: Discussionmentioning
confidence: 99%